Increasing Career Decision-Making Self-efficacy Through Solution-Focused Career Counseling - Ryan Hidayat Rafiola; Wenny Hulukati; Idriani Idris; Aisyah Ummu Hamidah (Department of Guidance and Counseling, FIP, Undiksha, 2023)
The emergence of various new jobs means individuals must be confident in their career decisions. The problem for high school students is that students tend to need more confidence in deciding on the right career direction. This study aims to determine the effectiveness of solution-focused career self-counseling in improving high school students' career decision-making efficacy. This research method uses a quantitative approach with an experimental research type. The sampling technique in this research used a purposive sampling technique, and five subjects were obtained for the research. Researchers adapted an instrument from Taylor & Betz known as the CDMSE scale. They developed a counseling guide by adapting Burwell & Chen's concept, with the study's results showing increased research from low interpretation to high interpretation. Based on the results of this research, solution-focused career counseling can be used to increase students' career decision-making self-efficacy. This research implies that confidence in students' career decisions can be improved and maintained through solution-focused career counseling, creating valuable experiences with teachers and parents.